1997
DOI: 10.1038/39057
|View full text |Cite
|
Sign up to set email alerts
|

Transmissions to mice indicate that ‘new variant’ CJD is caused by the BSE agent

Abstract: There are many strains of the agents that cause transmissible spongiform encephalopathies (TSEs) or 'prion' diseases. These strains are distinguishable by their disease characteristics in experimentally infected animals, in particular the incubation periods and neuropathology they produce in panels of inbred mouse strains. We have shown that the strain of agent from cattle affected by bovine spongiform encephalopathy (BSE) produces a characteristic pattern of disease in mice that is retained after experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,117
7
36

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,802 publications
(1,187 citation statements)
references
References 26 publications
27
1,117
7
36
Order By: Relevance
“…Our conclusion is that L-type BSE is a more likely candidate for a bovine source of TME infection than typical BSE. In the scenario that a ruminant TSE is the source for TME infection in mink, this would be a second example of transmission of a TSE from ruminants to non-ruminants under natural conditions or farming practices in addition to transmission of typical BSE to humans, domestic cats, and exotic zoo animals ( 37 ). The potential importance of this finding is relevant to L-type BSE, which based on experimental transmission into humanized PrP transgenic mice and macaques, suggests that L-type BSE is more pathogenic for humans than typical BSE ( 24 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our conclusion is that L-type BSE is a more likely candidate for a bovine source of TME infection than typical BSE. In the scenario that a ruminant TSE is the source for TME infection in mink, this would be a second example of transmission of a TSE from ruminants to non-ruminants under natural conditions or farming practices in addition to transmission of typical BSE to humans, domestic cats, and exotic zoo animals ( 37 ). The potential importance of this finding is relevant to L-type BSE, which based on experimental transmission into humanized PrP transgenic mice and macaques, suggests that L-type BSE is more pathogenic for humans than typical BSE ( 24 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…38 It is now understood that vCJD reflects the transmission of BSE to humans via the consumption of infected beef. 13,[39][40][41][42][43] BSE AND VCJD IN BRITAIN, 1984BRITAIN, -1996 The origins of the BSE crisis in Britain have been traced to Sussex in December 1984, when a cow fell ill with a new clinical syndrome: tremor and incoordination rapidly leading to death. Within a few months, cows from all across Britain had succumbed to a similar constellation of symptoms.…”
Section: The Science Of Bsementioning
confidence: 99%
“…Uncertainty surrounding the question of whether BSE could cause human disease was, as of 1996, no longer justifiable: a series of experiments conducted in cattle, sheep, cats, and humans had demonstrated that BSE and vCJD were pathologically identical to each other and distinct from other TSEs. 48 Therefore, claims that the discovery of BSE in Canadian cattle "created unmanageable uncertainty" 49 must be reframed: the discovery of BSE in Canada established with certainty that a previously theoretical public health risk was now present in Canada and would have to be addressed appropriately. We contend that this did not occur, in that the Canadian government appears to have failed to appreciate the implicit public health implications of BSE.…”
Section: The Science Of Bsementioning
confidence: 99%
“…Bovine spongiform encephalopathy (BSE), which has killed more than 280,000 cattle worldwide, is a prion disease caused by the feeding of recycled prion-infected foodstuff to cattle [1]. In turn, variant Creutzfeldt-Jacob Disease (vCJD), which has claimed over 200 victims, appears to be caused by consumption of BSE-contaminated beef products [2].…”
Section: How Do Prions Enter the Body?mentioning
confidence: 99%